THE IMPACT OF INTERGOVERNMENTAL FISCAL TRANSFERS ON QUALITY OF HUMAN RESOURCES - Sangur, Korneles; Louhenapessy, Desry Jonelda; Sangur, Leonard Day Mas; Siregar, Irvan (Jurnal REP (Riset Ekonomi Pembangunan), 2025)
This study aims to determine the impact of physical, non-physical, and village fund as part of intergovernmental transfer policy on the quality of human resources in Maluku Province, Indonesia. Maluku Province has the quality of human resources as measured by the Human Development Index which is still below the national level. To overcome this problem, this research offers a solution by focusing research on the transfer funds to the regions allocated for human resource development, the novelty of this research is modelling the Special Allocation Fund into two namely physical and non-physical and adding village funds in the model. This research is a quantitative research type of panel data consisting of 11 districts / cities in Maluku Province for the period 2017-2023.  The results show that physical Special Allocation Fund has a negative and significant effect on the quality of human resources, Non-Physical Special Allocation Fund has an effect and village fund has a positive and significant effect on the quality of human resources. This research provides a reference for the central government to improve targets and maintain the achievement of development targets that focus on the human aspects of the transfer funds to the regions, and for local governments to make wise use of the transfer funds from the central government for regional development.